Spanish cinema and the rise of the auteur : the case of Isabel Coixet - Rothwell, Jennie (Trinity College (Dublin, Ireland). Department of Hispanic Studies, 2015)
This thesis builds on and contributes to work in the field of film authorship and auteurism, critically considering Spanish director Isabel Coixet as a prime example of a contemporary, self-styled auteur. Heavily influenced by French film criticism, especially that of critics who wrote for Cahiers du Cinema during the 1950s, the label of auteur as a singular, genius artist was first afforded to well known, critically acclaimed directors.
Embargo End Date: 2022-01-01
Keywords: Hispanic Studies, Ph.D.; Ph.D. Trinity College Dublin, 2015